USING THE MONTE CARLO METHOD IN TEACHING STOCHASTICS IN THE CONTEXT OF TRAINING MATHEMATICS TEACHERS TO IMPLEMENT STEM EDUCATION - Kramarenko, Tetiana (Physical and Mathematical Education, 2023)
Formulation of the problem. The introduction of STEM education is an urgent problem in education. The methodology for training mathematics teachers (014 Secondary Education. Mathematics) in the context of STEM education needs to be improved. The cross-cutting use of the Monte Carlo method in teaching stochastics is an engineering tool, the successful mastery of which will help integrate the knowledge and skills of students in mathematics and computer science, and to train teachers to implement STEM approaches in mathematics teaching. The purpose of the article is to highlight the author’s work on the implementation of STEM approaches in teaching stochastics. Materials and methods. The paper uses theoretical and empirical research methods: analysis to clarify the thesaurus of the study; analysis of scientific sources to identify important areas that should be focused on for the formation of STEM competencies of students; synthesis, observation of the educational process; systematization and generalization of research results; use of statistical criteria to determine shifts in the value of the feature (Wilcoxon criteria). Results. The cross-cutting use of the Monte Carlo method in teaching stochastics has a positive effect on the level of academic achievement of students and their readiness to implement STEM approaches in teaching students. Conclusions. The use of the Monte Carlo method as an engineering tool shifts the emphasis of learning from the theoretical to the experimental plane. The study found that the cross-cutting use of the Monte Carlo method in teaching stochastics has a positive effect on the level of academic achievement of students. The increase in the level of readiness of future teachers for further implementation of STEM approaches in teaching students has been experimentally confirmed.